2020
DOI: 10.1108/whatt-07-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality for relaunching tourism post-COVID-19: socially distant, virtually connected

Abstract: Purpose This paper aims to understand the various facets of augmented reality (AR) and to explore its prospects for supporting the relaunch of the tourism sector post-COVID-19 in accordance with the guidelines set out by WHO and UNWTO. Design/methodology/approach This study falls into the category of exploratory research. It is based on a systematic review of secondary data. Thematic content analysis has been adopted to trace out the various ways in which AR can be an aid in overcoming challenges in the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 29 publications
1
61
0
5
Order By: Relevance
“…Whereas tourism marketing in destinations is a well-known activity, the essence of these responsibilities changes when having to face a disaster and deal with its consequences [43][44][45]. Tourism management organizations, hotel establishments and other tourism and destination businesses should coordinate their promotion and marketing initiatives [46].…”
Section: Changes Detected In the Promotion Of The Tourist Destination During Covid-19mentioning
confidence: 99%
“…Whereas tourism marketing in destinations is a well-known activity, the essence of these responsibilities changes when having to face a disaster and deal with its consequences [43][44][45]. Tourism management organizations, hotel establishments and other tourism and destination businesses should coordinate their promotion and marketing initiatives [46].…”
Section: Changes Detected In the Promotion Of The Tourist Destination During Covid-19mentioning
confidence: 99%
“…ICT-based areas were used by a wide range of institutions, scholars, businesses, etc. preparing their meetings in the digital platforms (Mohanty et al, 2020). VR-based technologies can be an extremely helpful tool for MICE tourism (Pearlman & Gates, 2010) by protecting time and money (Gustafson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, in such periods that people don't want to travel to crowded places and desire to experience things that are needed less human interaction, VR technology can provide all types of experiences without physically participating in the activity or going to a destination (Buhalis & Motloka, 2013). In their study by Mohanty, Hassan, and Ekis (2020), they concluded that physical distancing and less mobility in the tourism industry will be pursued even after this outbreak. Thus, the demand for technologies based on VR is going to increase.…”
Section: Review Papermentioning
confidence: 99%
See 1 more Smart Citation
“…No estudo de Fontoura et al, (2020), que investiga os impactos da pandemia de coronavírus na indústria do turismo, as mudanças na demanda por sustentabilidade no turismo foram discutidas e os resultados indicaram que, embora o setor tenha parado quase inteiramente, há uma oportunidade para o renascimento de um turismo mais sustentável. Soluções como uso de realidade aumentada e turismo virtual também foram propostas (por exemplo, Mohanty et al, 2020). Apesar de serem opções válidas, dificilmente, porém, substituiriam o turismo real no mundo pós-pandemia, mas passariam a ser um complemento a ele.…”
Section: Relevância Do Estudounclassified